Investigation of Indoor Stability Testing of Polymer Solar Cell - Kavak, Pelin; Parlak, Elif Alturk (HINDAWI LTD, 2016)
We have fabricated organic solar cell of a new low bandgap polymer poly[4,4-bis(2-ethylhexyl)-4H-cyclopenta[ 2,1-b:3,4-b'] dithiophene-2,6-diyl-alt-4,7-bis( 2-thienyl)-2,1,3-benzothiadiazole-5',5''-diyl] (PCPDTTBTT). We have investigated for the first time the stability tests, ISOS-L-1 and ISOS-D-3, of PCPDTTBTT solar cells. Thermal annealing of PCPDTTBTT solar cells at 80 degrees C brought about an improvement of photocurrent generation, stability, and efficiency of the solar cells. T-80 value of PCPDTTBTT solar cell is about 150 hours which is close to P3HT (235h). PCPDTTBTT is very promising polymer for both polymer solar cell efficiency and stability.
Keywords: INTERNAL QUANTUM EFFICIENCY; MORPHOLOGY; Polymer Science